Mn(ii) tags for DEER distance measurements in proteins via C–S attachment. Issue 48 (17th November 2015) - Martorana, Andrea; Yang, Yin; Zhao, Yu; Li, Qing-Feng; Su, Xun-Cheng; Goldfarb, Daniella
Abstract : Tags for Mn 2+ –Mn 2+ distance measurements in proteins with a short and stable linker that generate narrow distance distributions were developed. Abstract : Mn 2+ chelating tags for Mn 2+ –Mn 2+ distance measurements by pulse EPR spectroscopy were developed. They feature a stable C–S conjugation to the protein, high reactivity towards cysteine thiols and short and rigid linkers that can be used in distance measurements with high resolution under reductive conditions. Double electron–electron resonance measurements at 95 GHz on ubiquitin labeled with these tags showed the expected narrow distance distribution.